Potenziale der Nordostpassage. - Leypoldt, Patrick (Deutscher Verkehrs-Verl., 2010)
Trotz zahlreicher Forschungsvorhaben fehlen detaillierte und aktuelle Aussagen zum künftigen Nutzungspotenzial der Nordostpassage, das sich aus den globalen Handelsströmen ergeben könnte. Die Forschungsarbeit "Potenziale der Nordostpassage bis 2050", deren zentrale Ergebnisse hier zusammenfassend dargestellt sind, will einen Teil dazu beitragen, diese Lücke zu schließen. Hauptziel der Untersuchung ist es daher, zukünftige Entwicklungsmöglichkeiten dieser Meeresstraße als Alternative zu den bestehenden Transitrouten einzuschätzen und das potenzielle Transportaufkommen für Transitrelationen auf der Nordostpassage zu quantifizieren.

In spite of extensive research, no detailed and up-to-date facts are at hand with regard to the potential benefits arising from the use of the Northeast Passage, which could be assessed by reference to existing global trade routes. The research project "Potential Benefits of the Northeast Passage until 2050" - whose main findings are summarized in this report - is intended to help close this gap to some extent. The main purpose of this research project was to ascertain this waterway's chances of future development as an alternative to the existing transit routes and to quantify the potential volume of traffic along the transit routes of the Northeast Passage. The outcome has shown that the current conditions for the use of this waterway on any large scale do not yet meet the requirements of the prospective clientele. The waterway's potential benefits, as assessed in this research project, do show evidence that the traffic potential looks favorable and may reach 411 mn tons by 2050.
Northeast Passage outlook potential until 2050.
Keywords: Verkehr; Fernverkehr; Güterverkehr; Wasserverkehr; Containerverkehr; Verkehrspolitik; Verkehrsweg; Wirtschaftlichkeit; Welthandel; Transportweg; Routenwahl; Grenzüberschreitender Verkehr